2014
DOI: 10.1186/preaccept-9899442101298089
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to prolonged neuromodulation in cortical cultures: an invariable return to network synchrony

Abstract: Background: Prolonged neuromodulatory regimes, such as those critically involved in promoting arousal and suppressing sleep-associated synchronous activity patterns, might be expected to trigger adaptation processes and, consequently, a decline in neuromodulator-driven effects. This possibility, however, has rarely been addressed. Results: Using networks of cultured cortical neurons, acetylcholine microinjections and a novel closed-loop 'synchrony-clamp' system, we found that acetylcholine pulses strongly supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 104 publications
3
17
0
Order By: Relevance
“…The synchronous slow oscillation appears to be the inherent property of cortical neuron assemblies because the oscillation can be found in ex vivo cortical slabs/slices ( Sanchez-Vives and McCormick, 2000 ; Timofeev et al, 2000 ). It was even shown that the cultured neurons exhibit a synchronous firing pattern similar to that of slow oscillation, and the synchronous firing pattern can be converted to asynchronous one by applying chemical(s) including excitatory neurotransmitters ( Hinard et al, 2012 ; Kaufman et al, 2014 ; Saberi-Moghadam et al, 2018 ). Overall, the synchronous slow oscillation of cortical neurons can be modulated through multiple layers of neurotransmitters, brain circuits, and neuronal networks.…”
Section: Hierarchical Organization Of Circadian Clocks and Sleep Homementioning
confidence: 99%
“…The synchronous slow oscillation appears to be the inherent property of cortical neuron assemblies because the oscillation can be found in ex vivo cortical slabs/slices ( Sanchez-Vives and McCormick, 2000 ; Timofeev et al, 2000 ). It was even shown that the cultured neurons exhibit a synchronous firing pattern similar to that of slow oscillation, and the synchronous firing pattern can be converted to asynchronous one by applying chemical(s) including excitatory neurotransmitters ( Hinard et al, 2012 ; Kaufman et al, 2014 ; Saberi-Moghadam et al, 2018 ). Overall, the synchronous slow oscillation of cortical neurons can be modulated through multiple layers of neurotransmitters, brain circuits, and neuronal networks.…”
Section: Hierarchical Organization Of Circadian Clocks and Sleep Homementioning
confidence: 99%
“…Recent investigations suggest that global processes, in particular neuromodulation, play important roles in brain network dynamics [ 13 , 14 ] by affecting neuron-astrocyte network communication [ 15 ]. Triggered by global changes (e.g., behavior or body temperature), neuromodulation regulates and stimulates brain activity by volume transmission, a process by which chemicals spread from the site of secretion through the brain extracellular fluid to affect a large number of cells [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Electrophysiological studies have shown that SSA states in the above situations share the same basic features (Sanchez-Vives and McCormick, 2000 ; Mao et al, 2001 ; Steriade et al, 2001 ; Cossart et al, 2003 ; Shu et al, 2003 ; Kaufman et al, 2014 ). As revealed by EEG or local field potential measurements, they are characterized by slow (< 1 Hz) network oscillations, consisting of epochs of high network activity intercalated with periods of nearly absent network activity.…”
Section: Introductionmentioning
confidence: 99%